Not All Heart Attacks are Created Equal: Thinking Differently About Acute Myocardial Infarction in the Young - Theresa Rizk; Ron Blankstein (Methodist DeBakey Cardiovascular Journal)
Cardiovascular disease, particularly myocardial infarction, remains a major cause of morbidity and mortality among young individuals. Although myocardial infarctions have declined significantly in the general population, this decline has not been uniformly observed in younger cohorts. Young adults often have different risk factors, including a higher burden of tobacco use and substance abuse, and they are less likely to be treated with preventive therapies since they are often categorized as having low risk. This review examines the existing literature on myocardial infarction in young patients, with a focus on risk factors, therapeutic challenges, and opportunities for prevention.